2011
DOI: 10.1186/1471-2407-11-385
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of weekly paclitaxel and capecitabine in patients with metastatic or recurrent esophageal squamous cell carcinoma

Abstract: BackgroundThis phase II study assessed the response rate and toxicity profile of weekly paclitaxel and capecitabine in patients with metastatic or recurrent squamous cell carcinoma of the esophagus (SCCE)MethodsPatients with histologically confirmed SCCE were treated with paclitaxel 80 mg/m2 intravenously on days 1 and 8 plus capecitabine 900 mg/m2 orally twice a day on days 1-14. Treatment cycles were repeated every 3 weeks until disease progression or unacceptable toxicity.ResultsBetween 2006 and 2009, 32 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The most common toxicity related to DDP was nausea/vomiting, as expected. Hematological toxicity, especially myelosuppression, was slighter compared with previous studies on taxane-based regimens in esophageal cancer 5,26. Only four patients experienced grade 3 adverse events.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The most common toxicity related to DDP was nausea/vomiting, as expected. Hematological toxicity, especially myelosuppression, was slighter compared with previous studies on taxane-based regimens in esophageal cancer 5,26. Only four patients experienced grade 3 adverse events.…”
Section: Discussionmentioning
confidence: 50%
“…Thus, it is important to find effective regimens for metastatic ESCC. It is reported that taxane-based regimens have demonstrated high clinical activities and survival advantages in metastatic ESCC,2631 and it was hypothesized that replacing PTX with solvent-free Nab-PTX might provide even better clinical benefits to patients with metastatic ESCC. Therefore, in this study, a novel formulation of Nab-PTX was explored for combination with DDP as a first-line regimen for patients with metastatic ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase II study, combined weekly paclitaxel and capecitabine proved to be a highly active regimen with a PFS of 5.23 months and an OS of 14.3 months. However, the cohort size was small with only 12 patients in the first-line setting [29]. Although direct comparisons are difficult across several trials due to different clinicopathologic patient characteristics, our study shows comparable efficacy and outcomes, especially the competitive median OS of 1 year, which has rarely been exceeded for metastatic ESCC despite the improvements in chemotherapy regimens and supportive care.…”
Section: Discussionmentioning
confidence: 74%
“…38-40) or second-line paclitaxel and capecitabine (45%; ref. 41). As such, the role of temozolomide monotherapy for CRC and esophageal cancer seems limited.…”
Section: Discussionmentioning
confidence: 99%